Production of probiotic kvass beverages enriched with pine nut shell extract and propionic acid bacteria - KHANTURGAEV, Andrey Germanovich; KHAMAGAEVA, Irina Sergeevna; SHIRETOROVA, Valentina Germanovna (Food Science and Technology, 2023)
The aim of this study was to develop a new functional product: a probiotic kvass beverage (PKB) based on curd whey with the addition of polyphenols from Pinus sibirica shell extract and propionic acid bacteria (PAB). The studies conducted have shown that replacing water with curd whey in the traditional technology for preparing kvass wort contributes to the active growth of yeast and the accumulation of alcohol. Therefore, it has been established that the separate cultivation of yeast and PAB is optimal. The optimal parameters for producing a product with the best consumer properties were determined: the dose of yeast starter, the amount of PAB concentrates, the quantity of pine shell extract, and the duration of the cultivation stages. Fermentation of whey-based fermented kvass wort with a concentrate of PAB and pine shell extract enriches it with propionic, acetic, and free amino acids (FAA) and B vitamins. Also, it improves the consumer properties of beverages and the quality and functional properties of the finished product. Tannins give the product a brown color and a pleasant tart taste. The high antioxidant activity of tannins contributes to preserving the quality of beverages during long-term storage. Pronounced antagonistic and antimutagenic activities of the resulting drink were established due to the combined action of yeast, PAB, and pine shell extract. Based on the research, a technology for producing a PKB was developed.